"Betrayed into the Hands of the Enemy": The 1795–96 Russian Investigation of the Death of Hedayat-Allah Khan of Gilan. Issue 2 (April 2022) - Gledhill, Kevin
Abstract: This article examines the Russian investigation of the death of Hedayat-Allah Khan, who ruled Gilan from the mid-1750s until his death in 1786. Using Russian consular reports and records of the 1795 Russian investigation of his death, the article offers two major conclusions. First, Hedayat-Allah Khan ruled a Caspian-centered polity linked to the Russian consulate and trade through partnerships with merchant intermediaries. As Qajar hegemony in Iran emerged by 1786, the consulate and merchants threw their support to Aqa Mohammad Khan. Second, the 1795 Russian investigation of his death was opened by Catherine II to solidify alliances in response to Qajar claims to Tiflis in 1795. Shifting Russian strategic priorities under Emperor Paul removed the need for this investigation.